A new psycho visual masking model for robust image watermarking - Ernawan, Ferda; Mustaffa, Zuriani; Mohamad, Fadli; Bayuaji, Luhur (2018)
Demand for access and sharing of the digital image through the internet, the digital image can easily be copied, edited and reused in communication nowadays. Digital image watermarking is an approach to protect and manage the intellectual property of digital images. A natural embedding watermark based on the human eye properties can be utilized to effectively hide a watermark image. Human visual system typically ignores visual redundant part of color image. This research proposed psychovisual threshold in image watermarking and image compression. In this research, the principle of psycho acoustic model has referred to develop a psychovisual threshold for robust image watermarking. Psychovisual threshold is able to determine the redundant area of the image for watermark embedding. The redundant information can be used to embed copyright of digital image. This project develop a robust image watermarking based on the psychovisual threshold and spatially along the edge. The psychovisual threshold has also been used to assign bit allocation in image compression. It can be used to determine an optimal bit for each pixel. This research will also investigate the sensitivity of the changes in DCT coefficients to the error reconstruction in order to generate a set of bit allocation. The experimental results show that the proposed embedding watermark scheme produces a strong resistance under different types of attack. The experimental result that watermarked image does not introduce visually imperceptible distortion to the host images. We also has applied psychovisual threshold to determine an optimal bits budget in image compression, the experimental results show that the proposed bit allocation can improve the image compression performance in terms of image quality and compression rate.